Diagnostic of investments for environmental conservation programs in Mexico City, 2000-2018 - Moreno Unda, Arcelia Amaranta; Perevochtchikova, María (Instituto de Ecología, A.C., 2021)
In the context of urban expansion, the importance of preserving ecosystem services that come from peri-urban territories is highlighted. In relation, various direct incentives for conservation (DIC) have been developed and applied; however, frequently there is an overlap of instruments and a lack of knowledge of total investments, therefore, the objective of this work has been to develop a first diagnosis of investments in environmental conservation programs in the Conservation Land of Mexico City, 2000-2018. For this, methodologically, the compilation and systematization of available official information (open data) from government programs at the federal and local levels were used, with the construction and analysis of a database of 500 documents (organized by institution, type of program, subprogram, year, amount, beneficiary), and visualization through a network of actors of formalized support ("provider-recipient"). As a result, the timeline of the DIC is presented, with investments by institution and total, and the main contributors and beneficiaries are identified. In the end, the investment amounts are compared with opportunity cost and future challenges are determined in terms of evaluating the effects of local programs, the effectiveness of the instruments and the analysis of the influence of the context on the effectiveness of the DIC.